Safety of creatine supplementation: analysis of the frequency of reported side effects in clinical trials - Adriana Gil; Drew E. Gonzalez; Kelly Hines; Diego A. Bonilla; Richard B. Kreider (Journal of the International Society of Sports Nutrition, 2025)
Background Individual studies have indicated that creatine monohydrate supplementation is generally well tolerated and not associated with clinically significant side effects. Nevertheless, anecdotal reports about side effects persist. This comprehensive analysis aimed to determine the frequency of side effects reported in 685 human clinical trials conducted on creatine supplementation.Methods We performed a comprehensive literature review on PubMed with the keywords “creatine” and “supplementation.” After compiling a list of clinical trials on creatine supplementation in humans, we evaluated each publication and developed a summary table of creatine studies. Based on the side effects reported in these studies, we created a side effect list of 35 types of side effects mentioned in these studies. We categorized the presence of side effects in these studies (No, Yes) to compare the number of studies reporting side effects in participants taking placebos (PLA) and creatine (Cr) supplements. We then recorded the frequency of the side effects reported in each study for the creatine and placebo groups. A zero frequency was assigned if a side effect from the list was not mentioned in the study. We then summed the total frequency of side effects reported for each study. We also categorized each study by supplement groups (creatine, placebo), sex (combined cohort, male, female, unspecified), age (children/adolescents less than 18 yrs, young adults between 18-45 yrs, middle-aged adults between 45-65 yrs, older adults more than 65 yrs), training status (clinical population with physical health issues, clinical populations with cognitive issues, untrained, recreationally active, trained, athletes, military), health status (apparently healthy, clinical populations), clinical category (apparently healthy, cardiometabolic/ cardiopulmonary conditions, neurological conditions, musculoskeletal conditions, renal conditions, and other), and type of creatine ingested (CrM compared to other forms including creatine HCl, Magnesium-Creatine, Creatine Citrate, Creatine Pyruvate, Creatine Methyl-Ester, Creatine H20, Creatine Nitrate, Creatyl-L-Leucine). These categories were used to determine study demographics, dosages, and whether studies reported side effects among participants in the PLA and Cr groups. If incomplete demographic information (e.g., body weight) was provided, we used an average population value to estimate relative creatine intake. The frequency of side effects was then analyzed by categories using General Linear Model multivariate and univariate analysis. Prevalence rates were determined by dividing the number of side effects reported by the total number of participants for the PLA and Cr-supplemented groups and multiplying times 100. The prevalence difference between the supplement groups was determined by subtracting the prevalence rate observed in the creatine group from the placebo group. Alpha levels and effect sizes (eta squared) are reported for each side effect.Results This analysis provides a more detailed assessment of whether Cr supplementation increased the incidence of side effects among participants taking Cr supplements compared to those consuming PLA. Multivariate analysis revealed no differences in the frequency of side effects reported between participants taking PLA and Cr supplements (p=0.340, np2=0.023). Univariate analysis showed that 13,452 participants ingested PLA while 12,839 consumed Cr supplements (p=0.411). Of these, 4.21% of participants ingesting PLA reported having a side effect, while 4.60% of participants consuming Cr supplements reported side effects (p=0.828). Most of the reported side effects were reported from one large clinical trial that involved high-dose creatine supplementation for up to 8 years (i.e., 437/566 or 77.2% PLA, 478/591 or 80.9% Cr). When the number of participants reporting side effects was considered from all studies, no differences were observed in the frequency of gastrointestinal/abdominal-related issues (PLA 4.05%, Cr 5.51%, p=0.820), muscle cramping/pain (PLA 0.07%, Cr 0.52%, p=0.085), or any other of the 33 side effects evaluated, including clinical markers of health and renal function.Conclusions This comprehensive analysis reveals that Cr supplementation does not increase the frequency of 35 side effects evaluated compared to those reported when taking PLA. These findings indicate that Cr supplements are well-tolerated in children through older adults and healthy and medically managed patient populations. Therefore, claims that Cr supplementation increases the risk of untoward side effects are unfounded. Based on these data, we urge lobbyists, policymakers, and health agencies to consult with leading creatine scientists and consider the full spectrum of scientific data before implementing restrictions with adverse public health and performance implications.